Characterizing postural oscillation in children and adolescents with hereditary sensorimotor neuropathy - Alves de Baptista, Cyntia Rogean de Jesus; Nascimento-Elias, Adriana; Lemos, Tenysson Will; Garcia, Beatriz; Calori, Paula Domingues; Mattiello-Sverzut, Ana Claudia (PLOS ONE, 2018)
Charcot Marie Tooth disease (CMT) has negative functional impact on postural control of children; however, it has not been widely studied. Stabilometry can provide insights about postural control and guide preventive interventions in immature perceptual and musculoskeletal systems as those seen in children with CMT. This cross-sectional study aimed to identify and interpret stabilometric variables that reflect the postural control of children with CMT. 53 subjects (age 6–17) were assigned to one of the two groups: CMT (15 males and 14 females with CMT) or Control (13 males and 11 females healthy). Quiet standing was tested in different conditions: with open and closed eyes on regular surface (open-regular, closed-regular) and foam surface (open-foam, closed-foam) using a force platform. The minimum of 2 and maximum of 3 trials of 30 seconds for each test condition provided the classical stabilometric variables and Romberg Quotient (RQv). CMT group showed increase of confidence ellipse area, mean velocity, mediolateral and anteroposterior velocities associated with decreased mean body oscillation frequency, as the complexity of tasks increased. CMT postural deficit was identified by greater and faster sway associated with these lower frequencies, when compared to Control.